Electrochemical Oxidative C−H Amination of Phenols: Access to Triarylamine Derivatives - Tang, Shan; Wang, Siyuan; Liu, Yichang; Cong, Hengjiang; Lei, Aiwen (Angewandte Chemie International Edition, 2018)
Dehydrogenative C−H/N−H cross‐coupling serves as one of the most straightforward and atom‐economical approaches for C−N bond formation. In this work, an electrochemical reaction protocol has been developed for the oxidative C−H amination of unprotected phenols under undivided electrolytic conditions. Neither metal catalysts nor chemical oxidants are needed to facilitate the dehydrogenation process. A series of triarylamine derivatives could be obtained with good functional‐group tolerance. The electrolysis is scalable and can be performed at ambient conditions. Undivided attention: An atom‐economical oxidative C−H amination of unprotected phenols was achieved by an external oxidant‐free electrochemical reaction. Under undivided electrolytic conditions, triarylamine derivatives were produced with high functional‐group tolerance along with H2 generation.